Are firms adopting a sustainable culture? Perspectives from the Mauritian business sector. (1st January 2015) - Kassean, Hemant; Beepat, Malvika; Gungaphul, Mridula
There is some consensus that if firms are to adopt a sustainable culture and achieve economic growth, they need to look at sustainability beyond its 'green' roots which are also supported by the economic, social and cultural performance of business. The purpose of this paper is to assess the extent to which firms in Mauritius are adopting a sustainable culture. A representative sample of 182 local companies took part in the survey which was carried out using face–to–face interview and online method. Statistical analysis was carried out and the Cronbach's alpha score for the overall questionnaire was 0.96, indicating a high degree of reliability. Regression analysis showed that 'social pillar' had the strongest effect on sustainability (β = 0.756), followed by 'cultural pillar' (β = 0.421), then the 'environmental pillar' (β = 0.369), whereas for the 'economic pillar' β value was 0.012 indicating that this had little effect on the dependent variable. Implications from these findings are discussed together with directions for further research.